Aspirin-triggered DHA metabolites inhibit angiogenesis - Vara-Messler, M.; Trevisi, L.; Zulato, E.; Ramaschi, G. E.; Risé, P.; Pinna, C.; Indraccolo, S.; Sala, A.; Bolego, C. (Frontiers in Pharmacology, 2025)
Background and aimBlood vessels supply oxygen, nutrients and provide gateways for immune surveillance. Since this network nourishes all tissues, vessel abnormalities contribute to many diseases, such as cancer. One of the potential targets for Docosahexaenoic Acid (DHA) in cancer is suppressing angiogenesis, a process of new blood vessel formation within tumors. In addition, aspirin (ASA) has antineoplastic effects that may be mediated, at least in part, by metabolites derived from acetylated COX-2. We aimed at determining the effect of DHA as well as its metabolites in angiogenesis, using in vitro as well as in vivo models.MethodsEndothelial cell (EC) proliferation, motility and capillary-like tube formation were determined by MTT, wound healing, Boyden and Matrigel assays, respectively. In vivo angiogenesis was measured by the Matrigel sponge model in mice. The biosynthesis of proresolving lipid mediators by ECs was determined by LC-MS-MS.Results and conclusionDHA, but not arachidonic acid (AA), at concentrations consistent with those reached in blood after fish oil supplementation, decreased EC migration in a time- and concentration-dependent manner. Pretreatment with ASA modulated cell migration already after 24 h, while both DHA and ASA decreased migration at longer incubation times without affecting viability. 17-hydroxy-DHA was detected upon incubation with DHA, and increased amounts were observed upon combined treatment with DHA and ASA, an increase that was associated to a synergic effect on EC migration. 17(R)-hydroxy-DHA (17R-HDHA), the metabolite resulting from acetylated COX-2 activity of DHA, reduced EC migration in a concentration-dependent manner. DHA in the presence of ASA, as well as 17R-HDHA, also reduced EC tube formation. These results were confirmed in vivo where both 17R-HDHA or its downstream metabolite 17RResolvinD1 were able to decrease microvessels density in a Matrigel sponge model. Overall, we demonstrated that DHA in the presence of ASA-dependent acetylation of COX-2 showed increased antiangiogenic effects, possibly resulting from its conversion to its hydroxylated derivatives.